Design and implementation of multiple user mobile robot following system - Hasan, Zahari (2015)
Recently automation product for intelligent robot is increasingly getting very common. By the help of intelligent robot technologies that increased comfort, greater safety and security, life has been becoming easier [1]. With this system, mobile robot can be controlled from any target. It is desirable in many applications for a mobile robot to track and follow a person. The purpose of this thesis is to detail the design and implementation of a mobile robot following system through the use of beacons and remote control encoder decoder. This project entailed the design and construction of a mobile robot with the capability of determining its location in reference to know reference points and correct address. The implementation involved the use of ultrasound to determine the distance between the robot and known reference points and infrared decoder and decoder to determine the correct leader. From the distance, the Cartesian coordinates for the robot’s location along the horizontal plane where determined. The produced robot was capable of navigating within a 2m by 2m square area successfully. Possible source of error can be attributing to round of error due to conversion from floating point to integer as well as errors within the reflection of ultrasound frequency used to synchronize beacon transmission.